Baicalin, Baicalein, and Lactobacillus Rhamnosus JB3 Alleviated Helicobacter pylori Infections in Vitro and in Vivo - Chen, Mu‐En; Su, Chiu‐Hsian; Yang, Jai‐Sing; Lu, Chi‐Cheng; Hou, Yu‐Chi; Wu, Jin‐Bin; Hsu, Yuan‐Man (Journal of food science, 2018)
Helicobacter pylori infection is associated with chronic gastritis, peptic ulcers, and gastric cancer. The flavonoid compounds baicalin and baicalein found in many medicinal plants exhibit an anti‐inflammatory effect. The administration of Lactobacillus strains reducing the risk of H. pylori infection is well accepted. In this study, the therapeutic effects against H. pylori infection of baicalin, baicalein, and L. rhamnosus JB3 (LR‐JB3), isolated from a dairy product, were investigated. Compared to baicalin, baicalein exhibited stronger anti‐H. pylori activity and cytotoxicity on human gastric cancer epithelial AGS cells. Baicalin and baicalein both suppressed the vacA gene expression of H. pylori and interfered with the adhesion and invasion ability of H. pylori to AGS cells, as well as decreased H. pylori‐induced interleukin (IL)‐8 expression. In the mice infection model, high dosages of baicalin and baicalein inhibited H. pylori growth in the mice stomachs. Serum IL‐1β levels and H. pylori‐specific serum IgM and IgA levels in mice treated with baicalin and baicalein were decreased. Moreover, a synergistic therapeutic effect of baicalein and LR‐JB3 on eradicating H. pylori infections was observed. Thus, administrating baicalin, baicalein, or LR‐JB3 for an H. pylori infection could offer similar therapeutic effects to administering antibiotics while not disturbing the balance of gut microbiota. This study revealed the effects of baicalin, baicalein, and LR‐JB3 on attenuating the virulence of H. pylori. The synergistic effect with baicalein and LR‐JB3 provides the experimental rationale for testing the reliability, safety, and efficacy of this approach in higher animals and perhaps ultimately in humans to eradicate H. pylori infections. Practical Application Baicalin and baicalein exert health promotion and avoidance of H. pylori infections by interfering with H. pylori growth and virulence. Lactobacillus rhamnosus JB3 was used to reduce the gastric inflammation caused by H. pylori infection.